From Bio-Prospecting to Field Assessment: The Case of Carvacrol Rich Essential Oil as a Potent Mosquito Larvicidal and Repellent Agent - Evergetis, Epameinondas; Bellini, Romeo; Balatsos, George; Michaelakis, Antonios; Carrieri, Marco; Veronesi, Rodolfo; Papachristos, Dimitrios P.; Puggioli, Arianna; Kapsaski-Kanelli, Vassiliki-Nafsika; Haroutounian, Serkos A. (Frontiers in Ecology and Evolution, 2018)
Contemporary legislation tends to increase limitation on the use of all synthetic pesticides, promoting bio-pesticides as a safer alternative. Bio-prospecting efforts for bio-pesticides provide results, which rarely reach the industry. Present essay elaborates on our efforts to chart the path from the laboratory bench to field assessment. Eight Mediterranean wild gathered foods provided the essential oils that were assessed as mosquito control agents against the Asian tiger mosquito (Aedes albopictus). Three Lamiaceae essential oils, derived from Satureja thymbra, Origanum onites, and Thymbra spicata presented carvacrol as principal component. All exhibited DEET-like repellent performance and total larvae mortality defining the carvacrol rich essential oil (CREO) as a promising mosquito control agent. A commercial variety of Origanum vulgare ssp. hirtum, was selected as CREO source and subjected to dose-response and eco-toxicity studies. We have found significant larvicidal (LC90 of 58,747 mg/L), and repellent (0,2 μL/cm2) properties, but also severe toxicity (LC90 of 12,806 mg/L) against Macrocyclops albidus. This last figure was the limit for the larvicidal field assessment; while for the repellent evaluation was used double the minimum indication (0,4 μL/cm2). CREO was tested per se as larvicidal agent, and emulsified for both repellent and larvicidal field activity. The emulsified CREO’s spatial repellent assessment showed maximum efficacy of 86% in day 1 that gradually declined in the following two days (81%, 69%). Both emulsified and crude CREO proved to be efficient larvicidal agents, with crude CREO (3 weeks) overrunning slightly the emulsified (2 weeks) in terms of endurance. Conclusively, CREO in its emulsified form may be considered as a promising mosquito larvicidal and repellent agent, applicable in both precautionary and emergency response measures.